Genetically modified glyphosate-tolerant soybean in the USA: adoption factors, impacts and prospects. A review - Bonny, Sylvie (Agronomy for sustainable development, 2008)
Transgenic crops are the subject of lively debate and controversy. Despite such controversy, transgenic soybean has undergone a rapid expansion. Among various types of transgenic crops, herbicide-tolerant crops appear to many to be of limited interest, especially in Europe. Nonetheless, herbicide-tolerant crops are the most widely spread in the world. Indeed, glyphosate-tolerant soybean was notably the most cultivated transgenic plant in the world in 2006. In the USA 91% of soybean was transgenic in 2007. How can this particularly significant diffusion in the USA be explained, and what are its impacts? Such issues are addressed in this article, using surveys, studies of numerous statistical data and literature analysis. A first section underlines the importance of soybean in the current development of transgenic crops in the world, and the favourable context for their expansion in the USA. Then follows an analysis of the advantages and drawbacks of transgenic soybean for American farmers. Factors explaining the rapid diffusion of transgenic soybean are also analysed. A comparison of transgenic versus conventional soybean reveals that transgenic glyphosate-tolerant soybean allows both the simplification of weed control and greater work flexibility. Cropping transgenic soybean also fits well with conservation tillage. Transgenic soybean has an economic margin similar to conventional soybean, despite a higher seed cost. The next section describes the evolution of the use of herbicides with transgenic soybean, and some issues linked to the rapid increase in the use of glyphosate. At the beginning a smaller amount of herbicides was used, but this amount increased from 2002, though not steadily. Nonetheless, the environmental and toxicological impacts of pesticides do not only depend on the amounts applied. They also depend on the conditions of use and the levels of toxicity and ecotoxicity. The levels of ecotoxicity seem to have somewhat decreased. The success of transgenic soybeans for farmers has led to a higher use of glyphosate as a replacement for other herbicides, which has in turn led to a decline in its effectiveness. However, the issue here is not only genetic engineering in itself, but rather the management and governance of this innovation. Finally, the prospects of transgenic soybean are addressed. Transgenic soybean with new traits should be placed on the market. The conclusion describes economic context of the development of the first transgenic crops.